The Concept of Plea Bargain in the Criminal Process System in Indonesia - Haeranah, Haeranah; Mirzana, Hijrah Adhyanti; Anas, Andi Muhammad Aswin; Iskandar, Ismail; Arifin, Arnita Pratiwi; Amri, Ulil; Normiati, Normiati (LAW REFORM, 2025)
The concept of plea bargaining in Indonesia's criminal justice system still lacks a clear and definitive standard. This study aims to examine the current application of plea bargaining in the Indonesian justice system and to explore an ideal framework for its implementation in the future. The research adopts a normative juridical approach. The findings reveal that plea bargaining remains a relatively new concept in Indonesian criminal law. The existing Criminal Procedure Code does not provide regulations for plea bargaining as an alternative method for resolving criminal cases outside of court. However, the Draft Criminal Procedure Code has introduced the concept under the term "special path" in Article 199, which allows for plea bargaining between judges, public prosecutors, and legal counsel. Plea bargaining has the potential to serve as a solution to challenges in sentencing and correctional systems, ensuring the principles of swift, simple, and cost-effective justice while safeguarding the rights of the accused and enhancing their role in legal proceedings.